Functional outcome of autologus platelet rich plasma injection as treatment for patients with plantar fascitis - Akki, Sandesh F.; Bhat, Nandakishore; H., Akshay; N., Akshata (International Journal of Research in Orthopaedics, 2024)
Background: Plantar fasciitis (PF) is the most common cause of pain that occurs in the heel, and approximately 11% to 15% of adults having foot symptoms require an expert care. Heel pain and tenderness are some of the common symptoms. Many conservatives methods are available, Platelet rich plasma is one of the safe and effective therapy in relieving symptoms. To describe the functional outcome of autologus platelet rich plasma as treatment for patients with plantar fasciitis. To describe any complications associated with the procedure. Methods: It is a prospective observational study 45 patients with chronic Plantar fasciitis aged above 18 years were included in the study. All the patients had a minimum of 3 months of symptoms, were selected based on the inclusion and exclusion criteria and underwent the same method of treatment. All patients had a baseline assessment of numerical pain score and were repeated at regular intervals post treatment. The PRP was prepared from venous whole blood. Results: Pain score was assessed at the time of injection. The mean pain score of all the patients was 8.614. Percentage pain relief showed 48% had 100% pain relief, 33% had more than 50% pain relief and 6% had less than 50% pain relief from the study. Conclusion: Autologous PRP injection is a safe and useful modality of treatment in the treatment of Plantar fasciitis. Maximum benefit after PRP injection was observed at 2 months and had sustained for at least 6 months.